Study of basic mechanical properties of recycled concrete with various recycled coarse aggregate mixes - Kai Wu; Feng Chen; Chuyang Chen; Shiqi Lin; Yang Nan (Građevinar)
Three kinds of recycled aggregate concretes (RACs), with six different replacement rates at four ages, are subjected to the standard cube axial compression test to study mechanical properties. Failure modes, compressive strength, stress-strain curves, peak strain, and elastic modulus of RACs are systematically analysed. In addition, three equations are proposed for RACs to describe the relationship between the compressive strength and replacement rate. Comparison between various equations of elastic modulus and test results is presented, and then three most suitable equations are established for three kinds of RACs, including necessary modifications, especially for RAC with mixed recycled aggregates.